2019
DOI: 10.1002/hyp.13534
|View full text |Cite
|
Sign up to set email alerts
|

Implication of evaporative loss estimation methods in discharge and water temperature modelling in cool temperate climates

Abstract: Evaporative flux is a key component of hydrological budgets. Water loss through evapotranspiration reduces volumes available for run‐off. The transition from liquid to water vapour on open water surfaces requires heat. Consequently, evaporation act as a cooling mechanism during summer. Both river discharge and water temperature simulations are thus influenced by the methods used to model evaporation. In this paper, the impact of evapotranspiration estimation methods on simulated discharge is assessed using a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…This is the traditional approach used by researchers and modellers, and consists of calibrating the CEQUEAU temperature module by using each of the individual selected CP sites separately. We used the Root Mean Square Error (RMSE) as the objective function, as the strong seasonality of river temperature inhibits the use of other metrics (e.g., NSE and KGE) commonly used for assessing the performance of discharge (rather than temperature) simulations (Ouellet‐Proulx et al, 2019). The RMSE for a given CP is estimated using the Equation (). italicRMSEgoodbreak=1ni=1ntrueŷtyt2,$$ RMSE=\sqrt{\frac{1}{n}\sum \limits_{i=1}^n{\left({\hat{y}}_t-{y}_t\right)}^2}, $$ where ytruêt$$ {\hat{y}}_t $$ and yt$$ {y}_t $$ are the simulated and observed values at each time step, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…This is the traditional approach used by researchers and modellers, and consists of calibrating the CEQUEAU temperature module by using each of the individual selected CP sites separately. We used the Root Mean Square Error (RMSE) as the objective function, as the strong seasonality of river temperature inhibits the use of other metrics (e.g., NSE and KGE) commonly used for assessing the performance of discharge (rather than temperature) simulations (Ouellet‐Proulx et al, 2019). The RMSE for a given CP is estimated using the Equation (). italicRMSEgoodbreak=1ni=1ntrueŷtyt2,$$ RMSE=\sqrt{\frac{1}{n}\sum \limits_{i=1}^n{\left({\hat{y}}_t-{y}_t\right)}^2}, $$ where ytruêt$$ {\hat{y}}_t $$ and yt$$ {y}_t $$ are the simulated and observed values at each time step, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…To our knowledge, no studies have compared the PCE with stream evaporation measured by in‐stream pans or an energy‐balance approach. However, the PCE or a variation thereof has been found to predict higher daily evaporation rates than empirical wind functions (Benyahya et al., 2010; Ouellet‐Proulx et al., 2019). Glose et al.…”
Section: Experience From the Literaturementioning
confidence: 99%
“…To our knowledge, no studies have compared the PCE with stream evaporation measured by in-stream pans or an energy-balance approach. However, the PCE or a variation thereof has been found to predict higher daily evaporation rates than empirical wind functions (Benyahya et al, 2010;Ouellet-Proulx et al, 2019). Glose et al (2017) found that the PCE predicted condensation during winter due to negative net radiation, which is physically unrealistic given that humidity gradients typically drive stream evaporation during winter even when net radiation can be chronically negative (e.g., Dugdale et al, 2018;Leach & Moore, 2010;Webb & Zhang, 1997).…”
Section: Experience From the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Ouellet-Proulx et al (2017a) studied ensemble water temperature forecasting using water temperature and flow assimilation. The model's source code for the evaporative heat loss module is improved (Ouellet-Proulx et al, 2019). However, deterministic modeling using CEQUEAU is still needed to assess the combined impact of flow regime change and climate change on the Nechako.…”
Section: Introductionmentioning
confidence: 99%